The paradise. Season two [videorecording (DVD)] - Vanderham, Joanna; Elliott, Emun, 1983-; Wight, Stephen, 1980-; Lancashire, Sarah, 1964- ([Publisher not identified], 2014)
The series begins a year after the dramatic events that saw Moray declare his love for Denise and lose The Paradise after breaking off his engagement to Katherine. The spurned Katherine has since married Tom Weston with a troubled history. Although she seems to be starting her life anew, her passion for Moray threatens to draw her back into a love triangle, competing with Denise. Moray and Denise are still at the forefront of fashion and innovation, are plotting to regain The Paradise.